Analysis of Factors Affecting the Restatement of Financial Statements - Kusmeylinda, Kusmeylinda; Wahidahwati, Wahidahwati; Mildawati, Titik (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
The convergence of IFRS has brought an impact on the changes of financial accounting standards in Indonesia. The variation provide an opportunity for the restatement of financial statements. Therefore, this study aimed to examine CEO turnover, earnings management, and audit quality on the restatement of financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of2014 to 2018. In this study, purposive sampling method was carried out to consider samples with predetermined criteria. The obtained data were about 376 and analyzed using logistic regression with the SPPS 24.0 tool. As the results of data analysis, this study indicated that the CEO turnover had a positive effect on restatement; the earnings management had a positive effect on restatement; and the audit quality had no effect on restatement of financial statements.